PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Rahmelia Ahyani; Windhy Puspitasari (Jurnal Akuntansi Trisakti, 2019)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on Financial Performance on Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM). The population used in this study is the Sub-Sector Services company of Property and Real Estate listed on the Indonesia Stock Exchange in 2013-2017. Data collection used purposive sampling method which aims to determine the samples taken with certain criteria and objectives, deliberate data collection to be included in the criteria according to the research. Based on sample collection techniques obtained as many as 175 companies.The results found that 1) Corporate Social Responsibility (CSR) had a significant positive effect on corporate financial performance as measured by ROA, 2) Corporate Social Responsibility (CSR) had a significant positive effect on corporate financial performance as measured by ROE, and 3) Corporate Social Responsibility (CSR) had a significant positive effect on the company's financial performance as measured by NPM. This research has implications for the property and real estate industry sector in improving its financial performance through CSR disclosure considering the higher the corporate social responsibility disclosure, the higher the company's financial performance.